Penerapan Kurikulum SMK 2013 Revisi 2018 Dalam Pelaksanaan Pembelajaran Di Provinsi Aceh - Hari Anna Lastya; Sri Wahyuni (PTE FTK UIN Ar-Raniry, 2022)
Changing the Indonesian government's policy on the curriculum occured so quickly. The SMK curriculum is revised every year. Currently, Vocational Schools in Aceh province are already using the 2013 revised 2018 curriculum. However, in its implementation, minority of teachers received the training on socializing the implementation of the 2013 revised 2018 curriculum. Thus, it becomes a problem for the aspect of teacher competence in understanding and implementing the 2013 revised 2018 curriculum. However, the purpose of this study, to find out the implementation of the 2013 revised 2018 SMK curriculum in the learning process in Aceh province. This research uses descriptive quantitative research methods. The research subjects involved 30 teachers on vocational subjects in the province of Aceh. The chosen instrument is a questionnaire. The results showed that 16.67% or as many as 5 respondents responded that the implementation of the 2013 revised 2018 curriculum was partially implemented. Furthermore, a total of 23.33% or 7 respondents stated that the implementation of the curriculum was categorized as mostly implemented, and last, 60% or 18 respondents stated that the implementation curriculum is categorized of fully implemented. It can be concluded that the implementation of the 2013 revised 2018 curriculum in the implementation of learning in Aceh province is in the fully implemented category. This is indicated by the obtained mean value of 50.38 which located in the class interval score (>48.75) with the category fully implemented.